Investigating the Academic Challenges of International Students: A Case Study at One Higher Education in Jambi - Abrar, Mukhlash; Wachyunni, Sri; Harjono, Hary Soedarto (Universitas Jambi, Magister Program of English Education Department, 2024)
The purpose of this study is to identify academic challenges experienced by 10 international students studying at one higher education in Jambi. To collect the data, focus group discussion was employed guided by a moderator from research team. The participants of this study were 10 first-year international students. Going through thematic analysis, researchers identified six academic challenges faced by international students, including lecturers’ inability to teach in English, limited support from local friends, lack of staff’s proficiency in English, limited material, punctuality in academic, and lack of English proficiency. Considering the encountered challenges, suggestions for university are provided in the paper.